Mary Wollstonecraft. ([Publisher not identified], 2020)
Gale Group Inc. of the Thomson Corporation presents a biographical sketch of English author Mary Wollstonecraft Godwin (1759-1797). The sketch highlights Godwin's childhood, her writings, her political views, and her personal life.